Finding Approaches to Exploring the Environmental Factors That Influence Copepod-Induced Trophic Cascades in the East China Sea - Tz-Chian Chen; Pei-Chi Ho; Gwo-Ching Gong; An-Yi Tsai; Chih-hao Hsieh (Diversity, 2021)
Copepods have been known to be able to cause an increase in phytoplankton through trophic cascades, as copepods consume heterotrophic protists that feed on phytoplankton. However, how the intensity of copepod-induced trophic cascades varies with environmental conditions remains elusive. We hypothesized that a higher proportion of large phytoplankton in the phytoplankton size distribution, a higher stoichiometric quality of phytoplankton, and a higher temperature could mitigate the intensity of a trophic cascade through increasing direct grazing on phytoplankton by copepods. To explore this issue, we quantified the intensity of a trophic cascade as the difference in phytoplankton concentration reduction by grazing using in situ incubations with and without copepods in the East China Sea. We then investigated the relationship between the intensity of trophic cascades versus the slope of the normalized biomass size spectrum (NBSS) of the phytoplankton community, the C:N ratio of particulate organic matter (POM), and temperature. We found that the intensity of trophic cascades weakly decreased with the NBSS slope and increased with temperature; however, both relationships were not statistically significant. We did not find a clear relationship between the strength of the trophic cascades and the C:N ratio of POM. Our results do not support the hypothesis that the proportion of large phytoplankton, the stoichiometric quality of phytoplankton, and the temperature affect trophic cascades. Instead, we suggest that other critical factors, such as protist abundance, play a role in affecting trophic cascades in the plankton food web in the East China Sea. We further propose some issues which should be addressed when conducting in situ shipboard incubation.